Implementation of occupational safety and health measures at German schools during the SARS-CoV-2 pandemic—cross-sectional results from 31,089 teachers - Koestner, Clemens; Eggert, Viktoria; Dicks, Theresa; Beutel, Till; Kalo, Kristin; Zähme, Carolina; Letzel, Stephan; Dietz, Pavel (Frontiers in Public Health, 2023)
Background The SARS-CoV-2 pandemic exacerbated existing health-related challenges in schools and created new ones. Under pandemic conditions, health risks increased, and with them the requirements for occupational safety and health (OSH) measures. The aim of the study was (a) to examine the status quo of OSH measures in German schools, (b) to analyze whether the implementation of OSH measures was associated with preferable outcomes and (c) to identify predictors for the implementation of OSH measures. Methods A nationwide cross-sectional online survey was conducted among teachers at all school types in Germany in March 2021. Data on the implementation of OSH measures (risk assessments, infection protection instructions and instructions on occupational safety), associated health-related parameters (e.g., somatic symptoms, PHQ-15) and predictor variables (e.g., gender, age or federal states) were assessed using descriptive statistics, analysis of variance and multiple linear regression analysis. Results Less than 10% of surveyed teachers (N = 31,089) reported that their schools met legal requirements for occupational safety and health measures. Beneficial associations became apparent where more measures were implemented, e.g., significantly better somatic and mental health. Predictors for the implementation of OSH measures were found, especially on a systemic level (e.g., federal states schools were located in). Conclusions Our study can serve as a basis for future studies. It provides a status quo regarding the implementation of, associations with and predictors for OSH measures in German schools. Our results are best understood as evidence-based arguments to encourage political decision makers to improve the implementation of OSH measures in German schools and thereby foster teachers' health.